Diversity Oriented Clicking (DOC): Divergent Synthesis of SuFExable Pharmacophores from 2‐Substituted‐Alkynyl‐1‐Sulfonyl Fluoride (SASF) Hubs. (4th June 2020) - Smedley, Christopher J.; Li, Gencheng; Barrow, Andrew S.; Gialelis, Timothy L.; Giel, Marie‐Claire; Ottonello, Alessandra; Cheng, Yunfei; Kitamura, Seiya; Wolan, Dennis W.; Sharpless, K. Barry; Moses, John E.
Abstract: Diversity Oriented Clicking (DOC) is a unified click‐approach for the modular synthesis of lead‐like structures through application of the wide family of click transformations. DOC evolved from the concept of achieving "diversity with ease", by combining classic C−C π‐bond click chemistry with recent developments in connective SuFEx‐technologies. We showcase 2‐S ubstituted‐A lkynyl‐1‐S ulfonyl F luorides (SASFs) as a new class of connective hub in concert with a diverse selection of click‐cycloaddition processes. Through the selective DOC of SASFs with a range of dipoles and cyclic dienes, we report a diverse click‐library of 173 unique functional molecules in minimal synthetic steps. The SuFExable library comprises 10 discrete heterocyclic core structures derived from 1, 3‐ and 1, 5‐dipoles; while reaction with cyclic dienes yields several three‐dimensional bicyclic Diels–Alder adducts. Growing the library to 278 discrete compounds through late‐stage modification was made possible through SuFEx click derivatization of the pendant sulfonyl fluoride group in 96 well‐plates—demonstrating the versatility of the DOC approach for the rapid synthesis of diverse functional structures. Screening for function against MRSA (USA300) revealed several lead hits with improved activity over methicillin. Abstract : Diversity‐oriented clicking (DOC) is a unified click chemistry approach for the synthesis of diverse lead‐like structures. Herein DOC is showcased through the application of novel highly activated 2‐s ubstituted‐a lkynyl‐1‐s ulfonyl f luoride (SASF) hubs in combination with a range of selective and robust click cycloaddition reactions, delivering an unprecedented SuFExable library of functional biologically active lead structures.